A Novel Integrative Mechanism in Anxiolytic Behavior Induced by Galanin 2/Neuropeptide Y Y1 Receptor Interactions on Medial Paracapsular Intercalated Amygdala in Rats - Narváez, Manuel; Borroto-Escuela, Dasiel O.; Santín, Luis; Millón, Carmelo; Gago, Belén; Flores-Burgess, Antonio; Barbancho, Miguel A.; Pérez de la Mora, Miguel; Narváez, José; Díaz-Cabiale, Zaida; Fuxe, Kjell (Frontiers in Cellular Neuroscience, 2018)
Anxiety is evoked by a threatening situation and display adaptive or defensive behaviors, found similarly in animals and humans. Neuropeptide Y(NPY) Y1 receptor(NPYY1R) and Galanin(GAL) receptor 2(GALR2) interact in several regions of the limbic system, including the amygdala. In a previous study, GALR2 enhanced NPYY1R mediated anxiolytic actions on spatiotemporal parameters in the open field and elevated plus maze, involving the formation of GALR2/NPYY1R heteroreceptor complexes in the amygdala. Moreover, the inclusion of complementary ethological parameters provides a more comprehensive profile on the anxiolytic effects of a treatment. The purpose of the current study is to evaluate the anxiolytic effects and circuit activity modifications caused by coactivation of GALR2 and NPYY1R. Ethological measurements were performed in the open field, the elevated plus-maze and the light-dark box, together with immediate early gene expression analysis within the amygdala-hypothalamus-periaqueductal gray(PAG) axis, as well as in situ proximity ligation assay to demonstrate the formation of GALR2/NPYY1R heteroreceptor complexes. GALR2 and NPYY1R coactivation resulted in anxiolytic behaviors such as increased rearing and head-dipping, reduced stretch attend postures and freezing compared to single agonist or aCSF injection. Neuronal activity indicated by cFos expression was decreased in the dorsolateral paracapsular intercalated(ITCp-dl) subregion of the amygdala, ventromedial hypothalamic nucleus(VMH) and ventrolateral part of the periaqueductal gray(vlPAG), while increased in the perifornical nucleus of the hypothalamus(PFX) following coactivation of GALR2 and NPYY1R. Moreover, an increased density of GALR2/NPYY1R heteroreceptor complexes was explicitly observed in ITCp-dl, following GALR2 and NPYY1R coactivation. Besides, knockdown of GALR2 was found to reduce the density of complexes in ITCp-dl. Taken together, these results open up the possibility that the increased anxiolytic activity demonstrated upon coactivation of NPYY1R and GALR2 receptor was related to actions on the ITCp-dl. GALR2-NPYY1R heteroreceptor complexes may inhibit neuronal activity, by also modifying the neuronal networks of the hypothalamus and the periaqueductal gray. These results indicate that GALR2/NPYY1R interactions in medial paracapsular intercalated amygdala can provide a novel integrative mechanism in anxiolytic behavior and the basis for the development of heterobivalent agonist drugs targeting GALR2/NPYY1R heteromers, especially in the ITCp-dl of the amygdala for the treatment of anxiety.